Manajemen Konflik Pada Lembaga Keuangan Syariah Dalam Perspektif Islam - Muhsinin Muhsinin (ITB AAS INDONESIA Surakarta, 2023)
In carrying out the sharia concept, Islamic financial institutions do not only focus on the practice of the contract, but also cover the entire existing system including the handling of conflicts that occur, but these conflicts are usually resolved using conventional-based conflict management, the purpose of this This research is conducted to examine conflict management in Islam so that it can be practiced in Islamic financial institutions. This research uses normative economic studies research methods with a literature review approach, this kind of method is used to examine research objects in accordance with Islamic norms or rules, the data used is primary data in the form of Al-Qur'an, hadith, books salaf books and secondary data in the form of books, journals and documents related to conflict management. The results of this study are that conflict management practiced in Islamic financial institutions has complied with the rules set by Islam by making compromises (deliberations), accommodation (yielding) for the sake of common interests, but the most important thing in overcoming conflicts in Islam is to have noble goals. by not harming other people in the sense that the main goal is to get happiness in the afterlife not for the sake of the world alone, because this is what really distinguishes it from conventional conflict management.